2022
DOI: 10.1111/tpj.15762
|View full text |Cite
|
Sign up to set email alerts
|

MaMYB4 is a negative regulator and a substrate of RING‐type E3 ligases MaBRG2/3 in controlling banana fruit ripening

Abstract: Fruit ripening is a complex developmental process, which is modulated by both transcriptional and posttranslational events. Control of fruit ripening is important in maintaining moderate quality traits and minimizing postharvest deterioration. In this study, we discovered that the transcription factor MaMYB4 acts as a negative regulator of fruit ripening in banana. The protein levels of MaMYB4 decreased gradually with banana fruit ripening, paralleling ethylene production, and decline in firmness. DNA affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…In addition, as previous work has revealed that MaWRKY49/111 physically interact with MabZIP21 [ 25 ], further investigations were needed to study the biochemical and genetic machinery of how MabHLH28, MaWRKY49/111, and MabZIP21 proteins act together to mediate banana fruit ripening and softening. Moreover, given the previous findings that MaMYB4 interacts with MaBRG2/3 and MaMAPK14 to undergo protein modifications [ 62 , 63 ], functional connectivity between MabHLH28 and the proteins involved in protein modifications presents opportunities for stripping away MabHLH28 under post-translational regulation during fruit ripening in a future direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, as previous work has revealed that MaWRKY49/111 physically interact with MabZIP21 [ 25 ], further investigations were needed to study the biochemical and genetic machinery of how MabHLH28, MaWRKY49/111, and MabZIP21 proteins act together to mediate banana fruit ripening and softening. Moreover, given the previous findings that MaMYB4 interacts with MaBRG2/3 and MaMAPK14 to undergo protein modifications [ 62 , 63 ], functional connectivity between MabHLH28 and the proteins involved in protein modifications presents opportunities for stripping away MabHLH28 under post-translational regulation during fruit ripening in a future direction.…”
Section: Discussionmentioning
confidence: 99%
“…DAP-Seq was conducted by the procedure previously described by Yang et al. [ 62 ]. The gDNA was extracted from banana fruit to construct the sequencing library.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell‐free and in vivo protein degradation tests were conducted as described previously (Yang et al, 2022). MaRZF1‐His fusion proteins exhibited transient expression in the N. benthamiana leaf tissue for cell‐free degradation assay, and the total proteins were subsequently extracted.…”
Section: Methodsmentioning
confidence: 99%
“…These results demonstrated that the MdMAPK3-MdNAC72 signaling module plays an important role in apple fruit ripening [ 59 ]. A study by Yang et al (2022) [ 31 ] showed that the protein level of the TF MaMYB4 decreased along with banana fruit ripening, which was coupled with ET production and a decline in firmness. MaMYB4 could bind to the promoters of a series of ripening-associated genes, including ET biosynthetic and cell-wall-modifying genes.…”
Section: Roles Of Mapk Signaling In Fruit Development and Ripening As...mentioning
confidence: 99%